Дослідження Дюрбе хана Хаджі Герая у 2008 р. - Ібрагімова, А.М.; Гаврилюк, Н.О. (Археологічні дослідження в Україні, 2009)
The paper is devoted to the research of shrine of Khan Haci Giray. 18 burials which were made from 1466 to 1551 have been studied. The wooden tombs were covered with the rich palls (velvet with gilded silver threads), and the buried were wrapped in the silk shrouds. This shrine in Dürbe is probably a single Khans’ burial in the Crimea which has not been robbed.